Subjects’ strategies against lordship in Burgundian and Habsburg Flanders - De Waele, Tom (Rural history, 2024)
From the thirteenth until the 18th century, the county of Flanders knew a special citizen status for rural residents. Country dwellers, normally residing under the jurisdiction and fiscality of lordships, could register themselves as external citizens or ‘ outburghers’ . Outburghership has primarily been researched within the context of state building and urban studies. This contribution prioritizes the perspective of the countryside. Studies on premodern Flanders have shown that the counts and cities tried to undermine the power of local lords by providing as many seigneurial subjects as possible with fiscal and judicial exemptions to the lords’ justice and taxes. The accessibility of outburghership and its varying appeal along time and space has not been adequately researched. This study argues that the heyday of outburghership in Flanders was between 1300 and 1550. After 1600, outburghership endured as defence mechanism against seigneurial lordship until both institutions met their demise in 1795.